Comparative Analysis of Bursaphelenchus xylophilus Secretome Under Pinus pinaster and P. pinea Stimuli - Silva, Hugo (2021)
The pinewood nematode (PWN), Bursaphelenchus xylophilus, the pine wilt disease's (PWD) causal agent, is a migratory endoparasitic nematode skilled to feed on pine tissues and on fungi that colonize the trees. In order to study B. xylophilus secretomes under the stimulus of pine species with different susceptibilities to disease, nematodes were exposed to aqueous pine extracts from Pinus pinaster (high-susceptible host) and P. pinea (low-susceptible host). Sequential windowed acquisition of all theoretical mass spectra (SWATH-MS) was used to determine relative changes in protein amounts between B. xylophilus secretions, and a total of 776 secreted proteins were quantified in both secretomes. From these, 22 proteins were found increased in the B. xylophilus secretome under the P. pinaster stimulus and 501 proteins increased under the P. pinea stimulus. Functional analyses of the 22 proteins found increased in the P. pinaster stimulus showed that proteins with peptidase, hydrolase, and antioxidant activities were the most represented. On the other hand, gene ontology (GO) enrichment analysis of the 501 proteins increased under the P. pinea stimulus revealed an enrichment of proteins with binding activity. The differences detected in the secretomes highlighted the diverse responses from the nematode to overcome host defenses with different susceptibilities and provide new clues on the mechanism behind the pathogenicity of this plant-parasitic nematode. Proteomic data are available via ProteomeXchange with identifier PXD024011.